2011
DOI: 10.1038/labinvest.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

In vivo, label-free, three-dimensional quantitative imaging of kidney microcirculation using Doppler optical coherence tomography

Abstract: Doppler optical coherence tomography (DOCT) is a functional extension of optical coherence tomography (OCT) and is currently being employed in several clinical arenas to quantify blood flow in vivo. In this study, the objective was to investigate the feasibility of DOCT to image kidney microcirculation, specifically, glomerular blood flow. DOCT is able to capture 3D data sets consisting of a series of cross-sectional images in real time, which enables label-free and non-destructive quantification of glomerular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 72 publications
2
43
0
Order By: Relevance
“…Finally, OCT can be performed using a thin flexible sterile endoscope or catheter [26,27] or even with a needle [28], enabling ease of use for minimallyinvasive procedures and the possibility of imaging deep within a solid tissue or organ. Previously, we have demonstrated that OCT is able to provide clinically relevant information (morphology and blood flow) using a rat kidney model [29][30][31]. In addition, we showed that OCT has sufficient penetration depth and resolution to visualize human kidney microanatomy on intact human kidneys ex vivo even when surrounded by an intact connective tissue renal capsule [32,33].…”
Section: Imaging Donor Kidneys To Determine Their Statusmentioning
confidence: 82%
See 2 more Smart Citations
“…Finally, OCT can be performed using a thin flexible sterile endoscope or catheter [26,27] or even with a needle [28], enabling ease of use for minimallyinvasive procedures and the possibility of imaging deep within a solid tissue or organ. Previously, we have demonstrated that OCT is able to provide clinically relevant information (morphology and blood flow) using a rat kidney model [29][30][31]. In addition, we showed that OCT has sufficient penetration depth and resolution to visualize human kidney microanatomy on intact human kidneys ex vivo even when surrounded by an intact connective tissue renal capsule [32,33].…”
Section: Imaging Donor Kidneys To Determine Their Statusmentioning
confidence: 82%
“…Blue-cyan represents blood flow in one direction while red-yellow represent blood flow in the opposite direction. In a previous publication, we have shown that DOCT will reveal glomerular blood flow and can be used to evaluate glomerular function/status [31]. …”
Section: In Vivo Oct Kidney Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, DOCT has had great success in the visualisation of ocular media and related flow dynamics (see Figure 26) [346][347][348][349], in addition to cerebral [350], cardiovascular [351] and urological [352] applications.…”
Section: Dopplermentioning
confidence: 99%
“…OCT is a high-resolution, cross-sectional, three-dimensional imaging modality [1][2][3][4][5][6][7][8]. We have studied OCT system and its application for over ten years [9][10], and have accumulated the enough knowledge for teaching.…”
Section: .Introductionmentioning
confidence: 99%